Oral soft tissue myxoma - Leena James; Akshay Shetty; Namitha Jaypal; Durga Okade (Wolters Kluwer Medknow Publications, 2012)
The intraoral soft tissue myxoma is an extremely rare, slowly growing, benign mesenchymal tumor. The myxomas are insidious, infiltrative tumors which occurred in all age groups, with an average patient age of occurrence of 38 years. Most frequent locations were the cheek, floor of the mouth and palate. The lesions were present from 2 weeks to 6 years prior to treatment. The recommended therapy is surgical resection with adequate margins. We present a rare case report of soft tissue myxoma arising from the tongue in a 62-year-old male patient.